Identification of stress as a predisposing factor in minor recurrent aphthous stomatitis: A case report - Samsul, Samsul; Mandasari, Masita; Rahmayanti, Febrina (Hasanuddin University, 2022)
Objective: The purpose article is to identify stress predisposing factors in patients with minor RAS.Methods: A 22-year-old woman came to Dental Hospital Faculty of Dentistry UI with complaints of canker sores pain in lower front gums for 4 days ago. Canker sores occur repeatedly every month, especially when there are lots of college assignments. Intraoral examination revealed a single ulcer, clear borders, oval-shape, a pink shallow base surrounded by erythema, size 3x2 mm in attached gingival, region 41-42, with tenderness. Screening for psychological conditions with DASS-21 questionnaire, obtained scores of severe anxiety level and stress. The patient was diagnosed minor RAS with stress predisposing factors.Results: Based on the subjective and objective examinations, the patient was diagnosed with cheilitis and minor RAS with possible predisposing factors to stress and anxiety.Conclusion: Stress can be a predisposing factor for RAS, so managing stress in patient is important for controlling recurrence.